2018
DOI: 10.1007/s40195-018-0860-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Relaxation of a Ti36.2Zr30.3Cu8.3Fe4Be21.2 Bulk Metallic Glass: Experiments and Theoretical Analysis

Abstract: The dynamic mechanical relaxation behavior of Ti 36.2 Zr 30.3 Cu 8.3 Fe 4 Be 21.2 bulk metallic glass with good glass-forming ability was investigated by mechanical spectroscopy. The mechanical relaxation behavior was analyzed in the framework of quasi-point defects model. The experimental results demonstrate that the atomic mobility of the metallic glass is closely associated with the correlation factor χ. The physical aging below the glass transition temperature T g shows a non-Debye relaxation behavior, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(40 reference statements)
1
1
0
Order By: Relevance
“…In the study of Zr57Nb5Al10Cu15.4Ni12.6, aging increased with annealing temperature for Ta/Tg > 0.942 but did not fluctuate much for Ta/Tg < 0.942 [50] . In the current work, the decrease of aging with the increase of annealing temperature accords with the results of Ti36.2Zr30.3Cu8.3Fe4Be21.2 metallic glass [51] .…”
Section: Physical Aging Analysissupporting
confidence: 90%
“…In the study of Zr57Nb5Al10Cu15.4Ni12.6, aging increased with annealing temperature for Ta/Tg > 0.942 but did not fluctuate much for Ta/Tg < 0.942 [50] . In the current work, the decrease of aging with the increase of annealing temperature accords with the results of Ti36.2Zr30.3Cu8.3Fe4Be21.2 metallic glass [51] .…”
Section: Physical Aging Analysissupporting
confidence: 90%
“…In recent years, various efforts have been made to overcome this limitation. It has been reported that the formation of BMG composites (BMGCs) is an effective approach to improve the room-temperature plasticity of BMGs [5][6][7]. CuZr-based BMGs exhibit excellent glass-forming ability.…”
Section: Introductionmentioning
confidence: 99%